Non-Functional Requirements Elicitation Guideline for Agile Methods - Younas, M.; Jawawi, D. N. A.; Ghani, I.; Kazmi, R. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
One of the essential activities in software development is elicitation of requirement. Majority of the studies has pointed out that less attention is given to the NonFunctional Requirement (NFR). The negligence of NFR elicitation is due to lack of knowledge of the user and developer about NFR. Our study presents elicitation guidelines for NFRs in agile methods. This guideline will helps developers as well as users in agile methods. A case study is conducted on the group of master students for eliciting NFR with the help of elicitation guidelines. In addition, the initial results were obtained by extracting NFRs from eProcurement document that carries requirements of major European Union projects. The result of the case study is positive and encouraging for the new developers and users having less awareness about NFRs. Furthermore, the study describes the role of cloud computing in agile methods, especially in elicitation activity.